Morphological, nutritional and molecular characterization of selected genotypes for upland rice improvement through marker-assisted backcross breeding - Ferdous, Jannatul (2012)
Upland rice genotypes are low yielder but possess special traits. Marker assisted backcross breeding is a convenient technique for improvement of upland genotype in terms of yield and quality, where desirable trait is selected in early backcross generation. The aims of this study were to introduce high amylose content and high vitamin E alleles in BC1F1 generation as well as select the plant with desirable alleles through marker assisted selection (MAS) using SSR markers. Thirty nine rice genotypes were evaluated for parent selection based on morphology, nutritional composition, and genetic diversity. Three upland genotypes: Bukit Garam582, Bukit Garam1449, and Karingam were selected and back crossed with two high yielding varieties (BR16 and MR219). Identification of desirable plants for amylose content and vitamin E in BC1F1 generation was performed by MAS. The significant variation was observed among the genotypes for yield contributing characters, chlorophyll content, amylose content, glycemic index (GI), and antioxidant activity. The rice genotypes were grouped into 3 clusters, where Pulut Hitam Pahang (PHP), Lansan, and Karibang fell into 3 different solitary positions by morphological clustering. The first four principle components explained 76.5% variation for all morphological characters and showed positive correlation between tiller number, panicle number, filled grain percentage and grains per panicle. The highest apparent amylose content (27.1%) and the lowest GI (71.1) were observed in BR16. The highest GI (99.2) was found in Bukit Hitam (waxy rice) which contained low amylose (1.5%). The highest antioxidant activity (89.8%) was found in Karingam and the lowest (50.8%) was in BR16. The highest Fe, Zn, and Mg were observed in white and high yielding genotypes. The highest Mn and Cu were detected in local upland black genotype Bukit Hitam (54.4 μg/g) and red genotype Padi Hijau Manis (23.2 μg/g) genotypes, respectively. The genetic diversity was assessed using 25 SSR markers. Cluster analysis showed differentiation of rice genotypes into 4 major groups and several sub-groups. Cross and reciprocal cross in 10 combination between selected five genetically diverse parents were performed. The F1 plants were confirmed using Wx, RM190, RM3187, and RM3827 markers. The RM190 and Wx markers were used to select waxy allele for high amylose content. The RM3187 and RM3827 were used to select desirable allele of HGGT and HPT,respectively, which are responsible for tocopherols and tocotrienols biosynthesis. The following markers were amplified: for high amylose content (RM190 and Wx at 107 bp fragment); desirable allele of qTOC-6-2 (tocophelol) (RM3187 at 148 bp) and qT3-6-1 (tocotrienol) (RM3827 at 181 bp). A total of 28 plants were selected in BC1F1 generation, which contained all desirable alleles for high amylose content, tocopherol and tocotrienol. On the basis of morphological characters, plant number 9 of BR16/2 × Karingam (BC1F1) was selected for high yield potential. This plant produced the highest grain weight per plant (10.7 g) among 28 selected plants with 77.2% filled grain and grain color of this plant was white which can be used for the development of good quality and high yield potential upland variety.